THE EFFECTS OF MIND MAPPING TECHNIQUE TOWARDS STUDENTS` WRITING ARTICLE SKILL AT SMA NEGERI 14 KABUPATEN TANGERANG IN ACADEMIC YEAR 2017/2018 - Achmad Fachrurrozy (JIPIS, 2018)
Abstract This paper reports a study the effect of Mind Mapping technique towards students` writing article skill. The population in this research is all 10th grade students of SMAN 14 Kab. Tangerang. They are 240 students. The sample of this research is about 30 students which is taken from students who join English Club in the school. The research used experiment method where pre-test post test model was implemented. There were two kinds of tests; pre-test and post test to collect the data.Keywords: mind mapping, writing articles, writing skill  AbstrakMakalah ini menyajikan laporan pengaruh dari teknik Mind Mapping terhadap keterampilan menulis artikel siswa. Populasi dalam penelitian ini adalah semua siswa kelas 10 SMAN 14 Kab. Tangerang. Mereka adalah 240 siswa. Sampel penelitian ini adalah sekitar 30 siswa yang diambil dari siswa yang bergabung dengan Klub Bahasa Inggris di sekolah. Penelitian ini menggunakan metode eksperimen dimana model pre-test post test diimplementasikan. Ada dua macam tes; pre-test dan post test untuk mengumpulkan data.Kata kunci: keterampilan menulis, menulis artikel, mind mapping